Ministry Of Civil Aviation Decree No. 1103 of the Year 2024 Issued on 12/9/2024 Amending Certain Provisions of the Executive Regulations of the Civil Aviation Law Promulgated by Decree of the Minister Of Civil Aviation No. 1 of the Year 1989 =وزارة الطيران المدنى قرار رقم 1103 لسنة 2024 الصادر فى 12/9/2024 بتعديل بعض أحكام اللائحة التنفيذية لقانون الطيران المدنى الصادرة بقرار وزير الطيران المدنى رقم 1 لسنة 1989 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic